Witchcraft: gendered perspectives - Woodard, Jennie (Gendered perspectives, 2026)
"From fairy tales and fiction to Tiktok, the spectre of the witch has cast a long shadow over women and popular culture. Witchcraft: Gendered Perspectives traces the history of and evolution of the term "witch" across six centuries. Tracing the history of witchcraft from the publication of the Malleus Maleficarum to its contemporary representation and reclamation, this volume takes a gendered and intersectional approach to the cultural and historical shifts which have both demonised and democratised the witch online and in public discourse. Amongst these are: - The witch trials in Scotland, England, and America; - Literary and screen re-imaginings of the witch; - The rise of Wicca as an alternative religion. Witchcraft: Gendered Perspectives is an invaluable resource for graduate and undergraduate students across gender studies, queer history, religious studies, media studies, and European and North American history"-- Provided by publisher